Family functioning and adherence to medication: A study of hypertensive in a tertiary hospital, South Western Nigeria - Abayomi O Ayodapo; Kehinde Fasasi Monsudi; Olusegun Emmanuel Omosanya; Olayide Toyin Elegbede (Wolters Kluwer Medknow Publications, 2018)
Background: Hypertension is one of the most important risk factors for coronary heart disease, stroke, heart failure, and end-stage renal disease. It remains an important public health challenge, despite effective medical therapies for its management, patients' poor adherence remains a global problem. Aim: The main objective of this study is to determine the relationship between family functioning and medication adherence among hypertensive, attending a tertiary care center in South-West Nigeria. Materials and Methods: This was a descriptive cross-sectional study. The systematic sampling method was used to select 420 patients attending the outpatient clinic of the tertiary hospital. Relevant data were collected using interviewer-administered pretested semi-structured questionnaires. Results: Four hundred and twenty people participated in the study. The mean age of respondents was 60.97 ± 11.28 years, and a slight female preponderance (M:F = 1:1.7). Three hundred and forty-nine (83.1%) were married, 273 (65.0%) were from a monogamous family and 375 (89.2%) had a family size of >4. More than half of the study participants had a functional family (66.4%) and were adherent (61.2%) to their medication. Increased medication adherence proportion was observed in patients with a functional family. Adherence to medication is three times (odds ratio = 2.585, 95%CI = 1.636, 4.084) higher among patients with functional family. Conclusion: The structure and nature of family relationships, both of which determines family functioning, are important to medication adherence. A functional family enhances adherence to medication. Primary care physicians should create a positive treatment alliance with their patients to better family functioning.